EVOLUTION OF THE CRUST IN BELARUS RECORDED IN PALEODYNAMICS OF THE GRAVITY FIELD - Garetskii R.G.; Karataev G.I.; Dankevich I.V.; Golobokov S.Y. (My University, 2001)
Different stages of evolution of geological structures are recorded in time dynamics of their gravity field. The regularities of the crust evolution on the territory of Belarus were investigated through claculation and geological interpretetation of the gravity field dynamics in a succession of density models that reflect the main stages of the tectonic history of the region: Early Archean-Late Archean-Early Proterozoic-Riphean-Vendian-Late Paleozoic (Devonian-Carboniferous).
Keywords: Proterozoic; Devonian; Paleozoic; Vendian; Carboniferous; Riphean; Archean; Докембрий::Архей; Precambrian::Proterozoic; Precambrian::Proterozoic::Riphean; Precambrian::Proterozoic::Neoproterozoic::Vendian; Paleozoic::Devonian; Paleozoic::Carboniferous; Precambrian::Archean; Paleozoic; Палеозой::Девонская; Палеозой::Каменноугольная; Палеозой; Докембрий::Протерозой; Докембрий::Протерозой::Рифей; Докембрий::Протерозой::Неопротерозойская::Вендский